2010
DOI: 10.1111/j.1365-2443.2010.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulation of mitochondrial localization and stability of two human Sirt5 isoforms

Abstract: Seven human Sir2 homologues (sirtuin) have been identified to date. In this study, we clarified the mechanism of subcellular localization of two SIRT5 isoforms (i.e., SIRT5 iso1 and SIR-T5 iso2 ) encoded by the human SIRT5 gene and whose C-termini slightly differ from each other. Although both isoforms contain cleavable mitochondrial targeting signals at their N-termini, we found that the cleaved SIRT5 iso2 was localized mainly in mitochondria, whereas the cleaved SIRT5 iso1 was localized in both mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 52 publications
(85 reference statements)
8
67
0
Order By: Relevance
“…This amphipathic helix is then removed when the mitochondrial targeting signal is cleaved by the mitochondrial processing peptidase. Interestingly, the mitochondrial processing peptidase cleavage site of SIRT5 leaves an amphipathic helix on the mature protein at the extreme N terminus (12). This N-terminal amphipathic helix has three positively charged residues that orient into the solvent as seen in the SIRT5 crystal structure ( Fig.…”
Section: An N-terminal Amphipathic Helix Mediates Sirt5 Binding To Camentioning
confidence: 99%
“…This amphipathic helix is then removed when the mitochondrial targeting signal is cleaved by the mitochondrial processing peptidase. Interestingly, the mitochondrial processing peptidase cleavage site of SIRT5 leaves an amphipathic helix on the mature protein at the extreme N terminus (12). This N-terminal amphipathic helix has three positively charged residues that orient into the solvent as seen in the SIRT5 crystal structure ( Fig.…”
Section: An N-terminal Amphipathic Helix Mediates Sirt5 Binding To Camentioning
confidence: 99%
“…SIRT5 is broadly expressed with the highest expression levels in brain, heart, liver, kidney, muscles, and testis (99,102). SIRT5 is predominantly mitochondrial (33, 99, 102, 137); however, several reports have revealed the existence of functional extra-mitochondrial SIRT5 (46,96,116). In this regard, Park et al reported that a significant amount of SIRT5 is present in the cytosol in mouse hepatocytes and human 293T cells, and that a number of cytosolic and nuclear proteins, in addition to many mitochondrial proteins, were hypersuccinylated in the absence of SIRT5 (116).…”
Section: Sirt5 Regulates Newly Described Ptmsmentioning
confidence: 99%
“…An early study on SIRT5 identified two distinct human isoforms with only minor differences in the C-terminus (54). This study proposed a model where both isoforms of SIRT5 are targeted to the mitochondria for N-terminal processing, which can translocate out of the mitochondria to the cytoplasm and have varying degrees of protein stability (54).…”
mentioning
confidence: 99%